The utility of zebrafish cardiac arrhythmia model to predict the pathogenicity of KCNQ1 variants - Cui, Shihe; Hayashi, Kenshi; Kobayashi, Isao; Hosomichi, Kazuyoshi; Nomura, Akihiro; Teramoto, Ryota; Usuda, Keisuke; Okada, Hirofumi; Deng, Yaowen; Kobayashi-Sun, Jingjing; Nishikawa, Tetsuo; Furusho, Hiroshi; et al. (Journal of molecular and cellular cardiology, 2023)
Genetic testing for inherited arrhythmias and discriminating pathogenic or benign variants from variants of unknown significance (VUS) is essential for gene-based medicine. KCNQ1 is a causative gene of type 1 long QT syndrome (LQTS), and approximately 30% of the variants found in type 1 LQTS are classified as VUS. We studied the role of zebrafish cardiac arrhythmia model in determining the clinical significance of KCNQ1 variants. We generated homozygous kcnq1 deletion zebrafish (kcnq1del/del) using the CRISPR/Cas9 and expressed human Kv7.1/MinK channels in kcnq1del/del embryos. We dissected the hearts from the thorax at 48 h post-fertilization and measured the transmembrane potential of the ventricle in the zebrafish heart. Action potential duration was calculated as the time interval between peak maximum upstroke velocity and 90% repolarization (APD90). The APD90 of kcnq1del/del embryos was 280 ± 47 ms, which was significantly shortened by injecting KCNQ1 wild-type (WT) cRNA and KCNE1 cRNA (168 ± 26 ms, P < 0.01 vs. kcnq1del/del). A study of two pathogenic variants (S277L and T587M) and one VUS (R451Q) associated with clinically definite LQTS showed that the APD90 of kcnq1del/del embryos with these mutant Kv7.1/MinK channels was significantly longer than that of Kv7.1 WT/MinK channels. Given the functional results of the zebrafish model, R451Q could be reevaluated physiologically from VUS to likely pathogenic. In conclusion, functional analysis using in vivo zebrafish cardiac arrhythmia model can be useful for determining the pathogenicity of loss-of-function variants in patients with LQTS. [Display omitted] •Homozygous mutant zebrafish with deletion of the kcnq1 gene (kcnq1del/del) was created.•The ventricular APD90 of kcnq1del/del embryos was significantly longer.•It was shortened by co-injecting human KCNQ1 cRNA with human KCNE1 cRNA.•Injecting cRNA of pathogenic KCNQ1 variants did not rescue the prolonged APD90.•Injecting cRNA of KCNQ1 VUS, R451Q identified from a patient with LQTS did not rescue the prolonged APD90 either.